Sveti prostor v prepletu mitološke ideologije in simbolike kraja The Sacred Place: An Intertwining of Mythological Ideology and Spatial Symbolism - Boštjan Kravanja (Studia Mythologica Slavica, 2005)
The topic presented in this paper addresses the methodology of researching the sacred space and place. Since religious believes represent one of the most important anthropological fields, also the sacred places represent a heterogeneous theme, much reflected in the history of sciences.